25 Gbit/s transmission performance using duo-binary detection with 10 Gbit/s-PON receiver - Yongjia YIN; Yong GUO; Zhuang MA (Dianxin kexue)
IEEE has formed the 100 Gbit/s-EPON Task Force to develop next 100 Gbit/s-PON standards，and the duo-binary(DB) detection is one of the baseband technology options.25 Gbit/s DB detection transmission performance with 10 Gbit/s-PON receiver was been experimentally demonstrated.Because the bandwidth of 10 Gbit/s- PON receiver is obviously limited,the 25 Gbit/s DB output signal from 10 Gbit/s-PON receiver will be affected by the inter-symbol interference(ISI).The experiment results show that the system receiving sensitivity based on direct decision method is only -22 dBm.However,the system receiving sensitivity can be up to -24.5 dBm by using the most simplified maximum likelihood sequence estimation(MLSE) soft decision method.